The role of PI3k/AKT signaling pathway in attenuating liver fibrosis: a comprehensive review - Shamsan, Emad; Almezgagi, Maged; Gamah, Mohammed; Khan, Naveed; Qasem, Abdulkareem; Chuanchuan, Liu; Haining, Fan (Frontiers in Medicine, 2024)
Excessive accumulation of extracellular matrix (ECM) components within the liver leads to a pathological condition known as liver fibrosis. Alcohol abuse, non-alcoholic fatty liver disease (NAFLD), autoimmune issues, and viral hepatitis cause chronic liver injury. Exploring potential therapeutic targets and understanding the molecular mechanisms involved in liver fibrosis are essential for the development of effective interventions. The goal of this comprehensive review is to explain how the PI3K/AKT signaling pathway contributes to the reduction of liver fibrosis. The potential of this pathway as a therapeutic target is investigated through a summary of results from in vivo and in vitro studies. Studies focusing on PI3K/AKT activation have shown a significant decrease in fibrosis markers and a significant improvement in liver function. The review emphasizes how this pathway may prevent ECM synthesis and hepatic stellate cell (HSC) activation, ultimately reducing the fibrotic response. The specific mechanisms and downstream effectors of the PI3K/AKT pathway in liver fibrosis constitute a rapidly developing field of study. In conclusion, the PI3K/AKT signaling pathway plays a significant role in attenuating liver fibrosis. Its complex role in regulating HSC activation and ECM production, demonstrated both in vitro and in vivo, underscores its potential as a effective therapeutic approach for managing liver fibrosis and slowing disease progression. A comprehensive review of this field provides valuable insights into its future developments and implications for clinical applications.